Pengaruh E-Service Quality Terhadap E-Loyalty Melalui E-Satisfaction - Effendi, Reza; Musnaini, Musnaini; Suyoto, Yohanes Totok (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
ABSTRACT This research aims to determine the influence in the perspective of E-Service Quality, E-Loyalty and E-Satisfaction. This study used a quantitative method with the Partial Least Square (PLS) data analysis tool and assisted with SmartPLS 4.0 software. The subjects of this study were users of the Lazada e-commerce platform in Jambi City. The sampling technique used was purposive sampling. The number of samples used in this study was 100. The results showed that e-service quality had a positive and significant effect on e-loyalty, e-service quality had a significant effect on e-satisfaction, and e-satisfaction could affect electronic loyalty. With the e-satisfaction variable in this study can influence or mediate between e-loyalty and e-service quality variables, the findings of this study support a partial mediating effect. Keywords: E-Service Quality, E-Loyalty, E-Satisfaction.